The Use Of Philosophical Principles In English Teaching Modules - Puspitasari; Maisarah, Ira (UNIB Press, 2025)
This research aims to analyze the use of philosophical principles in the development and implementation of the teaching module. Teaching module is a collection of materials arranged according to a chronology, theme, or topic. Researchers examined how philosophical concepts like epistemology, axiology, ontology and teleology, were applied in the formulation, development, and implementation of the teaching module with a focus on the topic This is My School for seventh-grade. This study used document analysis method. The researcher investigated a lesson plan created by an English teacher at SMPN 30 Bengkulu Utara. Project-based learning was the approach that was used in the teaching module. The results of the study showed that the design and implementation of the teaching module were significantly affected by philosophical principles. In this module, epistemology shapes perspectives on how students learn knowledge and skills, while axiology highlights the importance of morality and values in education. Next, ontology encourages the use of differentiated teaching methods while educating and respecting the diversity of students. The last, teleology, emphasizes the need for particular goals to be set in order to focus learning and evaluate students' advancement toward these goals. The research findings provided deeper insights into the philosophical principles of the teaching module and how these principles impacted education in classroom practice. The implications of this research can contribute to more focused module development based on solid philosophical principles. Additionally, this study can serve as a foundation for further reflection and discussion within the context of student-centered learning.